2007
DOI: 10.1007/s00421-007-0612-7
|View full text |Cite
|
Sign up to set email alerts
|

The apoptotic response to strenuous exercise of the gastrocnemius and solues muscle fibers in rats

Abstract: The purposes of this study were to investigate the effects of strenuous exercise on apoptosis of the gastrocnemius and soleus muscle fibers and clarify the role of oxidative metabolism in the strenuous exercise-induced apoptosis. The experiment was designed with 49 (n = 49) male, 24-week-old, L. Wistar albino rats. Strenuous exercise model was applied to 42 (n = 42) rats and seven (n = 7) rats served as rested controls. All rats were randomly assigned to one of the following groups (n = 7): rested control (C),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
32
1
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(45 citation statements)
references
References 58 publications
(63 reference statements)
6
32
1
2
Order By: Relevance
“…Previous investigators found that the number of caspase-3 positive fibers is higher in rat soleus compared with tibialis anterior muscle following administration of clenbuterol (10) or angiotensin II (11). The percentage of apoptotic nuclei also increases rapidly in rat soleus muscle following strenuous exercise, but only gradually in gastrocnemius muscle (34). Bax levels also increase to a greater extent in soleus compared with gastrocnemius muscle following denervation; an effect suggested to be related to the higher mitochondrial content in soleus (4).…”
Section: Discussionmentioning
confidence: 90%
“…Previous investigators found that the number of caspase-3 positive fibers is higher in rat soleus compared with tibialis anterior muscle following administration of clenbuterol (10) or angiotensin II (11). The percentage of apoptotic nuclei also increases rapidly in rat soleus muscle following strenuous exercise, but only gradually in gastrocnemius muscle (34). Bax levels also increase to a greater extent in soleus compared with gastrocnemius muscle following denervation; an effect suggested to be related to the higher mitochondrial content in soleus (4).…”
Section: Discussionmentioning
confidence: 90%
“…Although our measurements were limited to 60 and 120 min of exercise, changes in some markers of apoptotic signaling would be expected at these time points if apoptosis was occurring. For example, treadmill running in rats lasting ϳ52 min has been shown to increase nuclei apoptosis as well as elevate caspase-3 and caspase-9 activity in skeletal muscle immediately after exercise (32). Furthermore, it has been reported that ARC protein is rapidly downregulated within 1-2 h following exposure of cells to apoptotic stimuli such as oxidant stress (45,46), an effect not accounted for by changes in ARC mRNA abundance (46).…”
Section: Discussionmentioning
confidence: 99%
“…Oxidative stress can induce myocyte apoptosis in vitro (27,64) and has been associated with elevated skeletal muscle apoptosis in vivo (13,32). Exercise has been shown to lead to oxidative stress (i.e., increased ROS formation, altered antioxidant levels, and oxidative damage to lipids, proteins, and/or DNA) in a number of animal and human tissues (reviewed in Refs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…12주간의 트레드밀 운동 훈련을 실시한 노후된 쥐의 비복근과 가자미근에서의 Bax의 발현은 감소되었고 동 일한 근육에서 Bcl-2의 발현이 증가되었다 [6]. 그러나 고강도 의 운동은 근섬유에서 apoptosis를 유발한다고 보고하였다 [17]. 이것은 apoptosis를 인위적으로 유도하기 위해 탈진적인 운동을 적용한것으로 근손상 과정에서의 apoptosis 반응일 것 으로 사료된다.…”
Section: 서 론unclassified